The Effect of Supply Chain Management on Firm Performance - Wafi, Azmi Zahran; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine and explain the effect of supply chain management on firm performance among webbing craft enterprises in Rajapolah Sub-District, Tasikmalaya, particularly amid increasing competition and challenges in raw material availability. Design/Methodology/Approach – This study employs a quantitative explanatory research approach. The research variables consist of supply chain management as the independent variable and firm performance as the dependent variable. The population includes 276 webbing craft MSME owners in Rajapolah Sub-District, Tasikmalaya. Using a probability sampling technique, 73 respondents were selected. Primary data were collected and analyzed using simple linear regression with SPSS version 26 to examine the relationship between supply chain management and firm performance. Findings – The results indicate that supply chain management has a positive and significant effect on firm performance. The regression coefficient of the supply chain management variable is 0.442, indicating that improvements in supply chain management contribute to increased business performance. These findings demonstrate that effective supply chain practices play an important role in enhancing operational efficiency and competitiveness among craft MSMEs. Originality/Value: This research provides value by offering empirical evidence on how supply chain management influences firm performance within the specific context of webbing craft MSMEs, a sector that has received limited academic attention. The study contributes original insights that can guide both practitioners and policymakers in strengthening operational strategies for local craft industries.